2009
DOI: 10.15288/jsad.2009.70.606
|View full text |Cite
|
Sign up to set email alerts
|

Attrition Bias in a U.S. Internet Survey of Alcohol Use Among College Freshmen

Abstract: ABSTRACT. Objective: Attrition bias is an important issue in survey research on alcohol, tobacco, and other drug use. The issue is even more salient for Internet studies, because these studies often have higher rates of attrition than face-to-face or telephone surveys, and there is limited research examining the issue in the fi eld of drug usage, specifi cally for college underclassmen. This study assessed whether measures of highrisk drinking and alcohol-related consequences were related to attrition groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 31 publications
(48 reference statements)
2
15
1
Order By: Relevance
“…At the individual level, many of our findings were consistent with previous literature. For instance, higher odds of nonresponse were seen in blacks and in men; similar results that have been replicated in many different samples of college students [ 17 , 23 - 25 ]. We also found that, compared with those seeking an advanced degree, those seeking a bachelor’s degree–but not those seeking an associate’s degrees–were more likely to be lost at follow-up, indicating a curvilinear relationship.…”
Section: Discussionsupporting
confidence: 59%
“…At the individual level, many of our findings were consistent with previous literature. For instance, higher odds of nonresponse were seen in blacks and in men; similar results that have been replicated in many different samples of college students [ 17 , 23 - 25 ]. We also found that, compared with those seeking an advanced degree, those seeking a bachelor’s degree–but not those seeking an associate’s degrees–were more likely to be lost at follow-up, indicating a curvilinear relationship.…”
Section: Discussionsupporting
confidence: 59%
“…Marijuana use may have been underreported (Akinci et al, 2001; Delaney-Black et al, 2010; Gruenwald and Johnson, 2006; Wagenaar et al, 1993), although measuring drug use in a school or research setting is more likely to produce honest responses (Kandel et al, 2006). The sample may also be subject to selection bias, given that substance users may have been less likely to continue participation in the study (McCoy et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Second, although follow-up data are weighted to account for its effects, sample attrition limits these data. Studies show that online surveys suffer from greater respondent attrition than other types of studies [45, 46] but that attrition does not necessarily indicate bias [47]. Third, observed dose-response effects are based on self-reported measure of exposure, which can be subject to selective attention biases.…”
Section: Discussionmentioning
confidence: 99%